IMPLEMENTASI KEBIJAKAN PENGELOLAAN OPERASIONAL TRANSPORTASI TRANS MAMMINASATA DI KOTA MAKASSAR - Amiruddin, Iswadi (Jurnal Ilmu Administrasi Negara, 2023)
This study aims to divert people to use public transportation with a descriptive research method. The results of this study indicate that the Aspect of Environmental Conditions indicates that the Trans Mamminasa Bus still has many shortcomings both in terms of narrow road contours and dense availability of bus stops, as well as the limited routes in the field which are still a separate task for the Makassar city government, The Inter-Organizational Relations Aspect shows that , all parties involved both from the South Sulawesi Provincial Transportation Service as an extension of the central government PT. Surveyor Indonesia as the supervisor and PT. Sinar Jaya Megah Lasting and PT. Borlindo as the operator, the Resource Aspect shows that the human and non-human resources used by the implementing operator, the Executing Agent Aspect supports the successful implementation of the Friends of the Trans Mamminasata Bus has proven that the ability of the executing agency is not in doubt.